Mekanisme Pertahanan Diri sebagai Bentuk Defensi Tokoh Hasan dalam Naskah Drama Sarapan Terakhir Karya Andrian Eka Saputra - Nida Amalia Manggala; Rudi Adi Nugroho (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The characters in every literary work have a conflict that makes the character experience anxiety and try to cover up his anxiety through self-defense. Self-defense mechanisms aim to protect a character or individual from external threats or impulses arising from internal anxiety. This form of self-defense is depicted through the character Hasan in the drama script "Sarapan Terakhir". This research aims to describe the self-defense mechanism of the main character Hasan in the drama script “Sarapan Terakhir” by Andrian Eka Saputra. This research uses a qualitative approach with literary psychology methods. The data collection technique used was reading and note-taking techniques. The data source in this research is a drama script in the drama script anthology "Sarapan Terakhir" by Andrian Eka Saputra. The results of this research show that there are four classifications of self-defense mechanisms in Hasan's character, including sublimation, rationalization, reaction formation, and projection.